Potential for eco-enzyme development as entrepreneurship in river ecotourism and mangrove conservation - Wijaya, Dika Putra; Laila, Nur (CV. Austronesia Akademika, 2024)
The development of tourism in Indonesia is currently experiencing rapid progress with the advancement of digital technology. The tourism sector is one of the factors that contributes greatly to the Indonesian economy. The biodiversity in Indonesia makes the tourism potential in Indonesia a source of pride, which is expected to become a more environmentally friendly tourism development. This study aims to determine the potential for eco-enzyme entrepreneurship in the Tegalsari Maritime Tourism Village by implementing ecotourism development and preservation strategies in Indonesia. Therefore, by doing entrepreneurship, it can improve the economy in the Tegalsari Maritime Tourism Village by making environmentally friendly superior products, one of which is eco-enzymes. This study is a qualitative research based on descriptive by analyzing the potential of entrepreneurship in the Tegalsari Maritim Tourism Village. This qualitative method based on descriptive is a type of research that describes in detail related to entrepreneurship studies in line with the aim of implementing ecotourism strategies. Based on the analysis conducted in this study, it can be concluded that the mangrove forest area in the Tegalsari Maritim Tourism Village has great potential to be used as a leading tourist destination in Malang Regency.